The constituent phase: the origins of Article 138 of the Constitution - Morana, Donatella (Toruńskie Studia Polsko-Włoskie, 2022)
The paper analyses the main issues that were tackled by the Constituent Assembly while devising article 138 of the Italian Constitution, which regulates the constitutional amendment process. After a brief analysis of the different positions that emerged during the debate, all united by a desire to “reinforce” the Constitution (i.e., to make it rigid), two important issues are examined. The first one regards the search for an amendment procedure that could reconcile the existing need for stability and continuity of the constitutional architecture, on the one hand, and the desire for renewal that could arise, on the other, in order to create a constitutional system that would be capable of matching social change. The various solutions for “reinforcing” constitutional amendment procedures that were considered by the Assembly are examined, along with their sets of problems, specifically in light of the subsequent implementation of article 138. The second one concerns the nature and the distinct meaning of the constitutional referendum as part of the constitutional amendment process, in the context of a broader debate on introducing direct democracy tools within legal systems based on representative democracy. Lastly, the paper focuses on the distinction between “laws amending the Constitution” and “other constitutional laws”, which is made in the first paragraph of article 138, investigating the meaning of said distinction in the system of sources and the different views on the topic that have emerged in the doctrinal debate.